Pengaruh Motivasi dan Kepribadian terhadap Organizational Citizenship Behavior dengan Budaya Organisasi sebagai Variabel Moderasi - Desi Nur Haryati (Universitas Proklamasi 45 Yogyakarta, 2019)
The phenomenon of development in the Srandakan sub-district as a route to Yogyakarta International Airport (YIA), a new airport in Kulon Progo, Yogyakarta affects public service needs. The staffs of Srandakan sub-district demanded to improve their self-quality which is reflected in organizational citizenship behavior (OCB). The purpose of his study is to find effects of motivation and personality on organizational citizenship behavior with organizational culture was put as a moderation variable. The sample used in this research is all personnel in the Srandakan sub-district office. In this study, the analysis was carried out using descriptive and inferential analysis methods. In order to conduct the inferential analysis of this study, the Partial Least Square (PLS), which is variance-based of structural equation model (SEM), is used as an analytical tool with SmartPLS 3.2.7 software. The result showed that no significant effect of motivation on Organizational Citizenship Behavior (OCB). Otherwise, there are signifi-cant effects of personality and organizational culture on organizational citizenship behavior. Finally, organizational culture can not be a moderating effect of motivation and personality on organizational citizenship behavior.